Serum homocysteine and folate levels as a predictor of materno-fetal outcome in preeclamptic women - Jain, Namita; Singh, Abha; Bhattacharjee, Jayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To study the role of serum homocysteine and serum folate levels in prediction of materno-fetal outcome in preeclamptic women, especially in early onset preeclampsia. Methods: This prospective study was conducted in a tertiary care teaching hospital in India. 60 preeclamptic women (Group A) that were matched with 60 normotensive pregnant women (Group B), with singleton pregnancy and gestational age between 24-32 weeks attending antenatal clinics were included in the study. Maternal blood was collected twice first at time of enrolment and second at delivery. Serum homocysteine and serum folate levels were analyzed using enzymatic assay and chemiluminescent immunoassay. Mean rise in serum homocysteine and folate levels were calculated individually in all patients. Results: Mean homocysteine levels were significantly higher in Group A as compared to Group B both at enrolment and delivery (p <0.05). Women with higher rise in mean homocysteine levels were associated with an increased risk of adverse maternal complications (p <0.05). Mean rise in homocysteine levels were significantly higher in women who developed abruption and perinatal death (p <0.05) while no correlation was found with the mean change in serum folate levels (p >0.05). Conclusions: Serum homocysteine can be used as a reliable marker for predicting the severity of preeclampsia and adverse pregnancy (both maternal and fetal) outcome thus helps in reducing maternal and fetal morbidity and mortality, especially in women with early onset preeclampsia.